Altered bone‐regulating myokine expression in skeletal muscle Of Duchenne muscular dystrophy mouse models. Issue 4 (3rd September 2018) - Zhou, Shumin; Qian, Baoli; Wang, Ling; Zhang, Changqing; Hogan, Macalus V.; Li, Hongshuai
ABSTRACT: Introduction: Duchenne muscular dystrophy (DMD) has been well characterized as a disease that affects both skeletal muscle and bone. The pathophysiology responsible for the deficits in bone tissue is still unclear. Methods: Quantitative reverse‐transcription polymerase chain reaction and Western blot analyses of known myokines from skeletal muscle were performed on dystrophic mouse models and wild‐type (WT) controls to identify differentially expressed bone‐regulating myokines. Results: Twenty‐four of 43 myokine genes demonstrated significantly different mRNA expression in the skeletal muscles of dystrophic mice when compared with muscles of WT mice. Several differently expressed bone‐regulating myokine genes were identified, and their protein levels were also verified by Western blot. Conclusions: Dystrophic skeletal muscle demonstrated a significantly altered myokine gene expression profile. mRNA and protein levels of several bone‐regulating myokines were significantly altered in dystrophic skeletal muscle, which suggests pathological role of bone‐regulating myokines on bone homeostasis in DMD. Muscle Nerve 58 : 573–582, 2018